Β‐Caryophyllene protects against alcoholic steatohepatitis by attenuating inflammation and metabolic dysregulation in mice. (22nd February 2017) - Varga, Zoltan V.; Matyas, Csaba; Erdelyi, Katalin; Cinar, Resat; Nieri, Daniela; Chicca, Andrea; Nemeth, Balazs Tamas; Paloczi, Janos; Lajtos, Tamas; Corey, Lukas; Hasko, Gyorgy; Gao, Bin; et al.
Abstract : Background and Aims: β‐Caryophyllene (BCP) is a plant‐derived FDA approved food additive with anti‐inflammatory properties. Some of its beneficial effects in vivo are reported to involve activation of cannabinoid CB2 receptors that are predominantly expressed in immune cells. Here, we evaluated the translational potential of BCP using a well‐established model of chronic and binge alcohol‐induced liver injury. Methods: In this study, we investigated the effects of BCP on liver injury induced by chronic plus binge alcohol feeding in mice in vivo by using biochemical assays, real‐time PCR and histology analyses. Serum and hepatic BCP levels were also determined by GC/MS. Results: Chronic treatment with BCP alleviated the chronic and binge alcohol‐induced liver injury and inflammation by attenuating the pro‐inflammatory phenotypic `M1` switch of Kupffer cells and by decreasing the expression of vascular adhesion molecules intercellular adhesion molecule 1, E‐Selectin and P‐Selectin, as well as the neutrophil infiltration. It also beneficially influenced hepatic metabolic dysregulation (steatosis, protein hyperacetylation and PPAR‐α signalling). These protective effects of BCP against alcohol‐induced liver injury were attenuated in CB2 receptor knockout mice, indicating that the beneficial effects of this natural product in liver injury involve activation of these receptors. Following acute or chronic administration, BCP was detectable both in the serum and liver tissue homogenates but not in the brain. Conclusions: Given the safety of BCP in humans, this food additive has a high translational potential in treating or preventing hepatic injury associated with oxidative stress, inflammation and steatosis. Linked Articles: This article is part of a themed section on Inventing New Therapies Without Reinventing the Wheel: The Power of Drug Repurposing. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.2/issuetoc